The Absence of Gumfoot Threads in Webs of Early Juveniles and Adult Males of Physocyclus globosus (Pholcidae) is not Associated with Spigot Morphology - Escalante Meza, Ignacio (2014)
Gumfoot threads attached to the substrate may allow spiders to retain prey. These threads were recently discovered in adult females of Pholcidae spiders, and are similar to those in Theridiidae. We report for the first time the presence of gumfoot threads in the webs of immature spiders of the pholcid Physocyclus globosus Taczanowski, 1874, and their absence in the webs of first and second instar juveniles and adult males. The bands of adhesive silk were shorter in fifth instar nymphs than in adult females, and had continuous rather than discrete adhesive droplets like the webs of two other adult female pholcid spiders. In Pholcidae, the large spigot on the anterior lateral spinnerets, which presumably produces glue, was relatively thicker in adult females and first instar juveniles than in adult males, which do not produce gumfoot threads. Therefore, we suggest that the ontogenetic origin of gumfoot threads may not be associated with changes in spigot morphology. In addition, the delayed production of gumfoot threads in P. globosus is different to theridiid spiders, in which spiderlings build gumfoot threads from emergence.